OPTIMASI KOMPOSISI SUKROSA DAN ASPARTAM SEBAGAI BAHAN PEMANIS PADA FORMULA TABLET-EFFERVESCENT EKSTRAK ETANOLIK BUAH MENGKUDU - Galih Pratiwi; Triana Hertiani; Mufrod Mufrod (Majalah Obat Tradisional, 2011)
Mengkudu (Morinda citrifolia L.) has been widely used as traditional medicine. Its unpleasant smell and flavor urge a more acceptable dosage formulation. The aim of this research was to optimize the composition of sucrose and aspartame as sweetening agent in effervescent tablet formulation by using Simplex Lattice Design method. Effervescent tablets were produced by fusion method in five (5) different formulas, i.e. formula I (100% sucrose), II (suucrose-aspartame=75%:25%), III (sucrose-aspartame=50%:50%), IV (sucrose-aspartame=25%:75) dan V (100% aspartame). Effervescent granules were evaluated for mass density, flowing time, tapping index and compactibility characteristics. The effervescent tablets were tested for weight uniformity, hardness, friability, and disintegration time characteristics as well as TLC profile chromatogram. Data was analyzed by one way ANOVA, Scheffe method and Kruskall-Wallis with significance level 95%. The tablet acceptability was tested among 30 respondents. The results showed that the different composition of sucrose-aspartame influence the physical characteristics of granules and tablets effervescent produced. More sucrose content will increase the hardness, lower the friability but prolong the disintegration time. 70% respondents chose formula III as the best formula. Evaluation of SLD data recommended sucrose and aspartame in 42:58 proportion as the most optimum formula.